2018
DOI: 10.1021/acs.langmuir.8b01621
|View full text |Cite
|
Sign up to set email alerts
|

Codeposition of Polydopamine and Zwitterionic Polymer on Membrane Surface with Enhanced Stability and Antibiofouling Property

Abstract: Although abundant works have been developed in mussel-inspired antifouling coatings, most of them suffer from poor chemical stability, especially in a strongly alkaline environment. Herein, we report a robust one-step mussel-inspired method to construct a highly chemical stable and excellent antibiofouling membrane surface coating with a highly efficient codeposition of polydopamine (PDA) with zwitterionic polymer. In the study, PDA and polyethylenimine-quaternized derivative (PEI-S) are codeposited on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 59 publications
(92 reference statements)
3
54
0
Order By: Relevance
“…Although alkaline desorption method has been commonly adopted for regenerating the Cr(VI)-adsorbed adsorbents, it was found that under strong alkaline conditions, PPMs will be aggregated, which result in low dispersibility and poor adsorption performance in the next adsorption cycle [51]. On the contrary, the regenerated PPMs via acidic condition demonstrate an outstanding dispersibility and maintain a good adsorption performance in the following cycles.…”
Section: Easy Regeneration and Recovery Of Adsorbents For Recyclingmentioning
confidence: 99%
“…Although alkaline desorption method has been commonly adopted for regenerating the Cr(VI)-adsorbed adsorbents, it was found that under strong alkaline conditions, PPMs will be aggregated, which result in low dispersibility and poor adsorption performance in the next adsorption cycle [51]. On the contrary, the regenerated PPMs via acidic condition demonstrate an outstanding dispersibility and maintain a good adsorption performance in the following cycles.…”
Section: Easy Regeneration and Recovery Of Adsorbents For Recyclingmentioning
confidence: 99%
“…“Zwitterionization” is a technology that involves grafting a zwitterion on the surface of a nanoparticle; various studies have been conducted on field of drug delivery systems [ 8 ] and antibacterial surfaces. [ 20,21 ] A zwitterion contains both positive (PCG) and negatively charged groups (NCG), thus forming a water bonded hydration layer stronger than PEG due to electrostatic interactions and hydrogen bonding with H 2 O molecules at an internally balanced pH value (net‐charge close to zero). [ 22,23 ] Replacing the hydration layer formed on the particle by the formation of a “protein corona” through binding with a protein is energetically unfavorable; therefore, it can prevent nonspecific adsorption and aggregation of particles and can provide the particle with “stealth” function.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Among all the approaches, surface coating of PDA is a very common strategy, and the PDA can be a versatile immobilization platform to covalently anchor another layer that can be a grafted superhydrophilic polymer chains or self‐assembled monolayer. [ 16,17 ]…”
Section: Figurementioning
confidence: 99%